(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The Economic belt of the Silk Road project (hereinafter referred to as the "EBSR") has formed China’s new long-term strategy "One belt − one way". With a view to the practical implementation of the EBSR initiative, China, in cooperation with interested Asian countries, is creating two important financial development institutions: the Asian Infrastructure Investment Bank and the Silk Road Fund. The new Chinese initiative, judging by the available information available, can pursue three strategic objectives: expansion of international and regional trade; the creation of international transport corridors from China to Europe and the Middle East through the territory of Kazakhstan and Central Asia; gradual increase of China’s economic presence in Central Asia as a strategically important partner. Kazakhstan, as well as other countries of Central Asia, it is important to participate in the implementation of the Chinese EEPS initiative, to effectively use the emerging new opportunities and advantages of regional cooperation, while achieving, at the same time, minimizing risks and threats.